Exploring the relationship between anastasis and mitochondrial ROS-mediated ferroptosis in metastatic chemoresistant cancers: a call for investigation - Cao, Yu; Lu, Chang; Beeraka, Narasimha M.; Efetov, Sergey; Enikeev, Mikhail; Fu, Yu; Yang, Xinyi; Basappa, Basappa; He, Mingze; Li, Zhi (Frontiers in Immunology, 2024)
Ferroptosis induces notablesignificant changes in mitochondrial morphology, including membrane condensation, volume reduction, cristae alteration, and outer membrane rupture, affecting mitochondrial function and cellular fate. Recent reports have described shed light on the intrinsic cellular iron metabolism and its intricate connection to ferroptosis, a significant kind of cell death characterized featured by iron dependence and oxidative stress regulation. Furthermore, updated molecular insights have underscored elucidated the significancecruciality of mitochondria in ferroptosis and its implications in various cancers. In the context of cancer therapy, understanding Field Code Changed the dual role of anastasis and ferroptosis in chemoresistance is crucial. Targeting the molecular pathways involved in anastasis may enhance the efficacy of ferroptosis inducers, providing a synergistic approach to overcomeing chemoresistance. Research into how DNA damage response (DDR) proteins, metabolic changes, and redox states interact during anastasis and ferroptosis can offer new insights into designing combinatorial therapeutic regimens against several cancersreatments associated with stemness. These treatments could potentially inhibit anastasis while simultaneously inducing ferroptosis, thereby reducing the likelihood of cancer cells evading death and developing resistance to chemotherapy. The objective of this study is to explore the intricate interplay between anastasis, ferroptosis, EMT and chemoresistance, and immunotherapeutics to better understand their collective impact on cancer therapy outcomes. We searched public research databases including goggle scholar, PubMed, relemed, and the national library of medicine related to this topic. In this review, we discussed the interplay between the tricarboxylic acid cycle and glycolysis has been implicated in modulating ferroptosis, adding complexity to its regulatory mechanisms. Additionally, the regulatory role of reactive oxygen species (ROS) and the electron transport chain (ETC) in ferroptosis has garnered significant attention. Lipid metabolism, particularly involving GPX4 and System Xc-plays a significantpivotal role in both the progression of ferroptosis and cancer. There is a pressing need to investigate the intricate interplay between anastasis, ferroptosis, and chemoresistance to better understand their collective impact on cancer therapy outcomes. Integrating anastasis, and ferroptosis into strategies targeting chemoresistance and exploring its potential synergy with immunotherapy represent promising avenues for advancing chemoresistant cancer treatment paradigms.